Mathematical model to predict the stability at ambient temperatures of Brevibacterium celere C-924 bacterium (2023)
Oxygen has been identified as one of the main causes leading to desiccation damage, while the time that the microorganism is exposed to ambient conditions can contribute to its degradation. At the Center of Genetic Engineering and Biotechnology of Camagüey, an ecological product with a solid formulation with proven bionematicidal action called HeberNem-S® was developed, whose active ingredient is the Gram-positive bacterium Brevibacterium celere C-924. In the present work, a stability study of the active ingredient of the HeberNem-SÒ product was carried out at temperatures of 16, 28 and 37 ºC without vacuum. As a result of the study, a mathematical model was obtained that simulates the degradation that occurs in the range of temperatures evaluated and without vacuum. The logarithmic-exponential mathematical model obtained makes it possible to estimate the degree of survival in the face of environmental modifications associated with the parameters studied, without the need to carry out experimental evaluations to determine viability.